The determinants of crude palm oil price in Malaysia / Muhammad Firdaus Abdullah - Abdullah, Muhammad Firdaus (2021)
In general, the crude palm oil industry has contributed significantly to the economy of Malaysia. Furthermore, Malaysia is the world's second largest palm oil producer and exporter in the world after Indonesia. However, the price of crude palm oil (CPO) is uncertain, and the trend shows a lot of fluctuations over the past 20 years. Due to the circumstances, the aim of the study is to investigate the macroeconomic variables that affected the crude palm oil prices in Malaysia from 1990 to 2019. Using the Ordinary Least Square (OLS) method, the effect of the independent variables which is money supply, foreign direct investment (FDI), inflation rate and interest rate will be examined. Data of the Malaysian crude palm oil price is used as the dependent variable while the other four variables, namely money supply, foreign direct investment (F DI), inflation and interest rate are used as independent variables. According to the findings, the data revealed that the interest rate has a considerable impact on the price of crude palm oil. Money supply, foreign direct investment (F DI), and inflation rate all had statistically minor effects on crude palm oil in Malaysia.